2021
DOI: 10.2147/jpr.s313868
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Humor Training for Patients with Chronic Pain: A Randomized Clinical Trial

Abstract: Background: Humor and laughter are positively associated with psychological as well as with physical well-being. As there is little research examining to what extent patients suffering from chronic pain could benefit from a humor intervention, the goal of this study was to develop a pain-specific humor training and to evaluate its feasibility and effectiveness as component of regular, multimodal pain therapy. Patients and Methods: Patients from inpatient treatment groups for chronic pain in a German hospital w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…First, the independent variable SEH was measured in the second wave. The justification is that self-enhancing comic style is a stable trait that generally does not change over time (Mesmer-Magnus et al, 2012;Hunter et al, 2016), with a few exceptions, such as those who receive systematic intervention in clinical settings (Kugler et al, 2021). SEH reinforced the results of our analysis despite the unusual order of measurement.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 61%
“…First, the independent variable SEH was measured in the second wave. The justification is that self-enhancing comic style is a stable trait that generally does not change over time (Mesmer-Magnus et al, 2012;Hunter et al, 2016), with a few exceptions, such as those who receive systematic intervention in clinical settings (Kugler et al, 2021). SEH reinforced the results of our analysis despite the unusual order of measurement.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 61%
“…Contemporaneous studies (located after data collection) support the use of humor with patients in a variety of ways and may enhance patients' own self-guided imagery. Humor training, focusing on the theory of humor and ways to see situations in new and humorous ways, (Kugler et al, 2021) showed promising results in reducing pain intensity and improving quality of life for hospitalized patients with chronic pain; and improving happiness and life satisfaction with female patients with epilepsy (Bagherzadeh Shirvan & Khodabakhshi-Koolaee, 2021). Watching comedy videos helped Turkish preoperative oncology patients have a significant reduction in anxiety, diastolic and systolic blood pressure suggesting that watching comedy videos had a positive effect on preoperative anxiety and blood pressure (Genç & Saritas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For individuals with chronic pain, in particular, humor has been shown to reduce pain intensity and decrease disruptions to quality of life. 32 Explicit humor therapy, in which individuals engage with materials they find entertaining, is associated with decreased pain and feelings of loneliness. 33 In this way, humor represents a nonpharmacological approach for addressing and even ameliorating pain.…”
Section: Humormentioning
confidence: 99%